Lethal aggression in mobile forager bands and implications for the origins of war - Fry, Douglas P; Söderberg, Patrik (Science (American Association for the Advancement of Science), 2013)
It has been argued that warfare evolved as a component of early human behavior within foraging band societies. We investigated lethal aggression in a sample of 21 mobile forager band societies (MFBS) derived systematically from the standard cross-cultural sample. We hypothesized, on the basis of mobile forager ethnography, that most lethal events would stem from personal disputes rather than coalitionary aggression against other groups (war). More than half of the lethal aggression events were perpetrated by lone individuals, and almost two-thirds resulted from accidents, interfamilial disputes, within-group executions, or interpersonal motives such as competition over a particular woman. Overall, the findings suggest that most incidents of lethal aggression among MFBS may be classified as homicides, a few others as feuds, and a minority as war.